Catalytic wet peroxide degradation of acrylonitrile wastewater by ordered mesoporous Ag/CeO2: synthesis, performance and kinetics. Issue 26 (29th April 2021) - Zhao, Guozheng; Liang, Hui; Xu, Hongzhu; Li, Changbo; Tan, Qingwei; Zhang, Daihang
Abstract : Ordered mesoporous Ag/CeO2 catalysts have been successfully synthesized by a microwave assisted soft template method. Abstract : Ordered mesoporous Ag/CeO2 catalysts have been successfully synthesized by a microwave assisted soft template method. The morphology, structure and chemical composition of the catalyst were characterized by XRD, N2 adsorption–desorption, SEM, EDS, TEM and XPS. The study of catalytic performance and reaction kinetics of organic matter degradation in acrylonitrile wastewater was performed in a catalytic wet peroxide (CWPO) system. The degradation pathways of organic matter in acrylonitrile wastewater were elucidated by temporal evolution of intermediates and final products detected by GC/MS analysis along with a continuous flow experiment study. The results show that the Ag/CeO2 has an ordered mesoporous structure, the specific surface area is 91.4–118.2 m 2 g −1 and the average pore size is 12.63–16.86 nm. 0.4-Ag/CeO2 showed the best catalytic performance, the COD removal rate reached 94.6%, which was 30% higher than that of CeO2 . The degradation is in accordance with the second-order reaction kinetics of the Arrhenius empirical model and Langmuir–Hinshelwood kinetic model. However the latter fits better, and the linear correlation coefficient R 2 is more than 0.98, which describes the adsorption catalytic mechanism of Ag/CeO2 . According to the analysis by GC/MS, the organic compounds in acrylonitrile wastewater oxidized into intermediate compounds and other small compounds, then are further oxidized into carbon dioxide and water. The catalytic activity of Ag/CeO2 was the result of the combination of Lewis acid–base position of CeO2 and redox cycle of Ce 3+ /Ce 4+ .